Study on the Morphologies of Poly(ethylene glycol)-block-poly(g-benzyl L-glutamate)-graft-poly(ethylene glycol) Aggregates Deposited from the Dilute Solution - Zhu, Guo-Quan; Wang, Fa-Gang; Li, Guo-Chang; Su, Chang-Hong; Liu, Yu-Ying (Asian Journal of Chemistry, 2013)
Poly(ethylene glycol)-block-poly-(g-benzyl L-glutamate)-graft-poly(ethylene glycol) (PEG-block-PBLG-graft-PEG) copolymer was synthe -sized by the ester exchange reaction of PBLG-block-PEG copolymer with mPEG. The surface morphologies of PEG-block-PBLG-graft-PEG copolymer aggregates from the dilute solution were studied by scanning electron microscopy. The effects of the solution concentration, the precipitation temperature and various solvent system on the surface morphologies of the polypeptide block-graft copolymer aggregates from the dilute solution were investigated.